2020
DOI: 10.3390/rs12182985
|View full text |Cite|
|
Sign up to set email alerts
|

Road Extraction from Very-High-Resolution Remote Sensing Images via a Nested SE-Deeplab Model

Abstract: Automatic road extraction from very-high-resolution remote sensing images has become a popular topic in a wide range of fields. Convolutional neural networks are often used for this purpose. However, many network models do not achieve satisfactory extraction results because of the elongated nature and varying sizes of roads in images. To improve the accuracy of road extraction, this paper proposes a deep learning model based on the structure of Deeplab v3. It incorporates squeeze-and-excitation (SE) module to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 53 publications
(57 reference statements)
3
17
0
Order By: Relevance
“…We concluded that these imperfections were caused by the complex nature of the geospatial object (roads have large curvature changes, different materials used in the pavement, different widths, depending on the importance of the route, and very often have no clearly defined borders) by the presence of occlusions in the scenes, and by the limitation of existing semantic segmentation algorithms. These imperfections and errors are in line with issues raised by other investigations, as similar problems were identified in other works tackling the road extraction task from high-resolution remote sensing images [2], [3], [4], [5], and are very problematic when pursuing a large-scale road extraction operation for automatic mapping purposes. As a consequence, we consider that adding a post-processing operation to improve the initial segmentation predictions is essential for a successful road extraction.…”
Section: Introductionsupporting
confidence: 82%
“…We concluded that these imperfections were caused by the complex nature of the geospatial object (roads have large curvature changes, different materials used in the pavement, different widths, depending on the importance of the route, and very often have no clearly defined borders) by the presence of occlusions in the scenes, and by the limitation of existing semantic segmentation algorithms. These imperfections and errors are in line with issues raised by other investigations, as similar problems were identified in other works tackling the road extraction task from high-resolution remote sensing images [2], [3], [4], [5], and are very problematic when pursuing a large-scale road extraction operation for automatic mapping purposes. As a consequence, we consider that adding a post-processing operation to improve the initial segmentation predictions is essential for a successful road extraction.…”
Section: Introductionsupporting
confidence: 82%
“…We also identified higher rates of "false positive labels in areas where the materials used in the road pavement have a similar spectral signature with their surroundings, or areas where geospatial objects with similar features are present (such as dry riverbeds, railroads, or irrigation canals) and higher rates of false negatives in sections where other objects cover large portions of the roads were covered" (page 13 in [8]). Similar problems are still observed in recent works dealing with the road extraction from high-resolution aerial imagery-improving the road extraction task is an active area of research [11][12][13][14].…”
Section: Introductionsupporting
confidence: 59%
“…The parameters τ , π y=1 and π y=0 are set to 1, 0.9 and 0.1, respectively. For validation, we compare the proposed loss with other commonly exploited losses for binary segmentation, including: 1) CE [6], [11]; 2) Dice; 3) NR-Dice [20]; 4) CE Dice [21]; 5) ELL [22]; 6) Weighted Dice (WDice); 7) BD Dice [15]; and 8) BD WDice. All the experiments are performed on an NVIDIA Tesla P100 GPU.…”
Section: A Experimental Setupmentioning
confidence: 99%